Upaya Guru Pendidikan Agama Islam Dalam Membina Akhlak Mulia Siswa Sekolah Dasar - Rosyid, M. Farhan; Septia Nugroho , Anggi; Fajri, M Rizkal (Universitas Majalengka, 2024)
Morals is among the great thinkers among Muslims whose influence is recognized and required right now. From a historical and theological perspective, morality appears to protect and direct Muslims on their path to safety in this life and the next, and it is not hyperbole to suggest that the primary goal of Muhammad's apostolate is the ideal growth of morality. That's what he stated, and history demonstrates that his preaching was successful in part because of the people who upheld his high moral standards, to the extent that Allah SWT personally commended the Prophet Muhammad SAW for his high moral standards and declared them to be uswah hasana. Human life patterns are determined by an individual's attitude towards God and the development of moral consciousness. Morals, sometimes known as morality, appropriateness, and propriety, are ethical principles that guide behavior. While an immoral life and every moral violation are in opposition to moral consciousness, a moral life and every moral deed are a suitable response to moral consciousness. Moral awareness is the state of self-consciousness in which individuals perceive or experience both good and harmful deeds.